Dose response of umeclidinium administered once or twice daily in patients with COPD: A pooled analysis of two randomized, double‐blind, placebo‐controlled studies. (24th June 2014) - Donohue, James F.; Kalberg, Christopher; Shah, Palvi; Beerahee, Misba; Mehta, Rashmi; Gunawan, Rudy; Church, Alison
Abstract Umeclidinium (UMEC) is an inhaled long‐acting muscarinic antagonist approved in the US and EU for the once‐daily (QD) treatment of chronic obstructive pulmonary disease (COPD); it is not indicated for the treatment of asthma. To fully characterize the dose–response relationship of UMEC in patients with COPD, a pooled analysis of data from two randomized, placebo‐controlled, cross‐over, dose‐ranging studies was performed, evaluating UMEC at doses of 15.6–1000 mcg QD and 15.6–250 mcg twice daily (BID). The primary endpoint was trough forced expiratory volume in one second (FEV1) at the end of each study's treatment period (Day 8/Day 15). A population model‐based analysis using total daily UMEC dose was used for the primary analysis comparing QD and BID dosing. A physiological effect (Emax) model was optimal in defining the relationship between UMEC dose and the primary endpoint, demonstrating a clear monotonic dose response over QD and BID dosing regimens. UMEC doses ≥62.5 mcg QD were differentiated from lower doses and BID dosing did not provide benefit over QD dosing. The potency (ED50) estimate was 33 mcg with QD dosing. These data indicate that UMEC 62.5 mcg and 125 mcg QD provide lung function benefits that warrant further investigation for the treatment of COPD.